Remote Learning in Clinical Nursing Education: A Lesson Learned from The Pandemic Covid-19 - Uswatun Khasanah; Karyadi Karyadi; Ayu Putri Senjaningrum; Dianis Wulan Sari (Universitas Airlangga, 2024)
Introduction: The clinical education program offers students a chance to gain practical experience, enabling them to acquire the skills and knowledge necessary to provide safe and effective nursing care. However, During COVID-19, modifying clinical education programs is essential to ensure continuity of nursing training while adapting to safety protocols and limitations on in-person interactions. This study aims to investigate how educational institutions modify and innovate nursing clinical education during pandemic situations. Methods: The study employed a descriptive exploratory design. The informants included ten mentors from various nursing education institutions in Indonesia who guide professional nursing students. The data were collected through in-depth, unstructured video call interviews. The data were collected through in-depth, unstructured video call interviews. Data analysis was conducted using content analysis. Results: The research found themes with 15 subthemes. These themes are: 1) learning constraints, 2) student challenges, 3) clinical educator challenges, and 4) teaching and learning opportunities. Conclusions: Professional education processes during a pandemic require better preparation in developing educational content, mastering various information technologies to support enhanced learning and the periodic evaluation of student competencies. This evaluation is necessary to ensure that students achieve the minimum competencies set by professional organizations.